Pentingnya pendidikan informal tentang ekonomi pada keluarga transmigran - Irma Suryani (Universitas Negeri Malang, 2017)
Educators are an important part of education, because educators are responsible for guiding and shaping their students. Parents act as educators in the family so that their daily attitudes and actions provide stimulus to the behavior of children. Parental errors in educating children can lead to children in their development are not able to independently and difficult to adapt to the environment. The process of economic education in the family environment, usually not programmed and scheduled so that the ongoing can happen at any time and may be incidental. In the process, exemplary and everyday attitudes of parents and the intensity of communication of children and parents in family life becomes an important point for economic education in the family. In addition, in everyday economic life is inseparable from the problem of money, the economic education in the family focused on the understanding of the value of money and order of attitudes and behavior of children to regulate the use of money in accordance with rational economic principles. Understanding of productive and economic activities in parents is important in the development of attitudes that can encourage the achievement of the effectiveness and efficiency of these activities conducted through economic education in the family environment. With the awareness of economic education within the scope of this family is expected to improve the economy of transmigrant families. KeywordsInformal Economy Education, Transmigrant Family http://dx.doi.org/10.17977/um022v2i22017p089